National Policy on Education and the Challenges of Girl-Child Education in Cross River State - Eyong, Victoria Amiokama (Kashere Journal of Politics and International Relations, 2023)
The importance of female education, especially in the developing countries, cannot be overemphasized. There is considerable evidence that the education of women has a direct impact on various aspects of the social, economic, and political well-being of a country. The study examined the National Policy on Education and the challenges of girl-child Education in Cross River State Mixed survey design was adopted for the study and a total sample of 295 respondents in Cross River State, Nigeria, participated in the study. The study was anchored on System Theory and findings showed that significant disparities in educational opportunities and the representation of girls in education. The consequences of limited educational opportunities for girls in Cross River State are far-reaching. The study recommends that Efforts should be made to improve access to quality education for girls. This includes the construction and renovation of school infrastructure, provision of safe transportation, and the implementation of policies that encourage and support girls’ enrolment and retention in schools.